'What shall be our new ornaments?' Description's orientations. Issue 4 (2nd April 2020) - Benson, Stephen
ABSTRACT: Description has made something of a comeback in recent years as part of a theorising of possibilities for a post-hermeneutical critical orientation. The present essay considers the descriptive turn, so-called, in relation to a range of writing that crosses the boundaries of the critical and the creative: in work by Claire-Louise Bennett, Lisa Robertson, Wayne Koestenbaum and R. F. Langley. The essay identifies in this writing an occupancy of description's register as it has been articulated over the ages by a frequently sceptical regulatory discourse: description as understood to be variously gratuitous, ornamental or passively affirmative. Rather than suggest an expanded field of contemporary descriptive practice, the proposal here is for description conceived as a minor mode, a relatively rare happening, but all the more valuable for being so.